1967
DOI: 10.1002/hlca.19670500810
|View full text |Cite
|
Sign up to set email alerts
|

Photoisomerisierung von Pyrazolen und Indazolen zu Imidazolen bzw. Benzimidazolen und 2‐Amino‐benzonitrilen

Abstract: It is shown that pyrazoles and indazoles undergo photochemical bond‐switching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
2

Year Published

1976
1976
2009
2009

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(15 citation statements)
references
References 12 publications
2
11
0
2
Order By: Relevance
“…Besides imidazoles themselves, other heterocyclic precursors can be used for the photochemical synthesis of heterocycles containing the imidazole nucleus. Photorearrangements of pyrazoles into imidazoles, which are generally obtained in low yields, have been reported; however, not all of these have been explained through the RCRE mechanism [2,3,5,37]. In fact, some experimental details have suggested that both the RCRE and ICI pathways are operative, and that open-chain intermediates are involved in some cases [5,38].…”
Section: Imidazolesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides imidazoles themselves, other heterocyclic precursors can be used for the photochemical synthesis of heterocycles containing the imidazole nucleus. Photorearrangements of pyrazoles into imidazoles, which are generally obtained in low yields, have been reported; however, not all of these have been explained through the RCRE mechanism [2,3,5,37]. In fact, some experimental details have suggested that both the RCRE and ICI pathways are operative, and that open-chain intermediates are involved in some cases [5,38].…”
Section: Imidazolesmentioning
confidence: 99%
“…Moreover, in analogy to the pyrazole-to-imidazole photorearrangement, N-unsubstituted benzimidazoles are obtained, in yields that are generally low (11-36%), by the photoinduced rearrangement of the corresponding indazoles [3,37]. On the other hand, high yields of 1-alkyl-benzimidazoles (73-96%) are claimed from preparative-scale irradiations of 2-alkyl-indazoles through an ICI rearrangement [3,37].…”
Section: Imidazolesmentioning
confidence: 99%
“…Few have much synthetic potential. [297,298] 12.4.2.1.2 Although 2-alkylindazoles are similarly transformed thermally into 1-alkylbenzimidazoles, the 1-alkylindazole isomers ring open to form 2-(alkylamino)benzonitriles.…”
Section: Synthesis By Ring Transformationmentioning
confidence: 99%
“…C 71,58 H 4,66 N 11,39% 1.4. 3,4-Bis(4-tolyl)sydnon (17). acetylchlorid wurde in Analogie zur Herstellung von a-Brom-a-phenylessigsaure-athylester [12] in a-Brom-u-(4-tolyl)essigsaure-athylester umgewandelt und dieser mit 4-Toluidin zum C, N-Bis(4-toly1)glycin-athylester umgesetzt.…”
Section: )) Diese Reaktionsweise Bietet F U R Alle Drei Nitriliumbetunclassified
“…Dreiring-Zwischenprodukte der Art 61 sind bei der Photoisomerisierung zahlreicher Sgliedriger Heterocyclen beobachtet worden (vgl. [17] und dort zit. Lit.).…”
unclassified